Pengaruh Model Problem Based Learning Berbantuan Media Wayang Kartun Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Setiawan, Sabrina Putri; Ramadhani, Amelia Fildza; Hamidah, Mutiara; Fauziah, Nur Destry; Rohimah, Femy Geria; Alindra, Afridha Laily (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
Research shows that elementary school students' critical thinking skills are relatively low, due to the use of conventional teacher-centered learning models. This study aims to determine the effect of the Wayang Kartun media-assisted Problem Based Learning model on the critical thinking skills of fifth grade students. This study used a pre-experimental method with a one-group Pretest-Posttest design. The research subjects were 22 fifth-grade students at an elementary school in Purwakarta Regency, consisting of 14 girls and 8 boys. The research instrument consisted of six HOTS-based essay questions compiled based on the FRISCO critical thinking ability indicators. Data were collected through Pretest and Posttest, then analyzed using the Shapiro–Wilk normality test, Levene's homogeneity test, and Paired Sample t-Test. The results showed an increase in critical thinking skills, from an average of 74.91% to 83.41%. The Paired Sample t-Test produced a Sig. (2-tailed) value of 0.000, confirming the significant effect of the use of the cartoon puppet-assisted Problem Based Learning model on students' critical thinking skills. These findings prove that the integration of the Problem Based Learning model with cartoon puppet media is effective in improving students' critical thinking skills, especially in science learning